Quality indicators for Barrett's endotherapy (QBET): UK consensus statements for patients undergoing endoscopic therapy for Barrett's neoplasia. Issue 4 (14th August 2019) - Alzoubaidi, Durayd; Ragunath, Krish; Wani, Sachin; Penman, Ian D; Trudgill, Nigel John; Jansen, Marnix; Banks, Matthew; Bhandari, Pradeep; Morris, Allan John; Willert, Robert; Boger, Phil; Smart, Howard L; et al.
Abstract : Introduction: Endoscopic therapy for the management of patients with Barrett's oesophagus (BE) neoplasia has significantly developed in the past decade; however, significant variation in clinical practice exists. The aim of this project was to develop expert physician-lead quality indicators (QIs) for Barrett's endoscopic therapy. Methods: The RAND/UCLA Appropriateness Method was used to combine the best available scientific evidence with the collective judgement of experts to develop quality indicators for Barrett's endotherapy in four subgroups: pre-endoscopy, intraprocedure (resection and ablation) and postendoscopy. International experts, including gastroenterologists, surgeons, BE pathologist, clinical nurse specialist and patient representative, participated in a three-round process to develop 15 QIs that fulfilled the RAND/UCLA definition of appropriateness. Results: 17 experts participated in round 1 and 20 in round 2. Of the 24 proposed QIs in round 1, 20 were ranked as appropriate (put through to round 2) and 4 as uncertain (discarded). At the end of round 2, a final list of 15 QIs were scored as appropriate. Conclusions: This UK national consensus project has successfully developed QIs for patients undergoing Barrett's endotherapy. These QIs can be used by service providers to ensure that all patients with BE neoplasia receive uniform and high-quality care.